SUPERVISI AKADEMIK KEPALA SEKOLAH UNTUK MENINGKATKAN WILLLINGNESS GURU - Yani, Ade Risma; Desyani, Khairiyah; Artati, Masyunila (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2024)
Academic supervision by school principals has a crucial role in increasing teachers' willingness to actively participate in professional development and improving the quality of learning. Given the importance of teacher willingness in the world of education, it should be the duty of school principals to continue to strive to improve teacher willingness in order to bring education to achieve goals and in a better direction. This study uses a literature review method on how the principal's academic supervision can affect teachers' willingness to improve their activities. The results of several previous reviews found that academic supervision carried out by school principals in a planned, structured and sustainable manner has a significant impact on increasing teacher willingness. Research shows that participatory supervision by involving teachers in planning and evaluation encourages teachers to be more thermotivation and willing to improve their competence in the learning process. The study concluded that the success of academic supervision depends on the principal's ability to communicate effectively, understand teacher needs, and create space for reflection and improvement. Therefore, strengthening the ability of school principals in academic supervision is very important to increase teachers' willingness to improve the quality of education.